PENGARUH PENGGUNAAN REFLEKTOR DAN PENDINGIN PASIF UNTUK MENGOPTIMALKAN DAYA KELUARAN PADA MODUL SURYA - Widodo Putra Halomoan Siregar; Moh Fawaid; Haris Abizar (Fakultas Teknik - Universitas Riau, 2022)
The objectives of this study were (1) To determine the effect of using passive reflectors and coolers on the output power produced by solar modules. The research method used was an experimental method with a true experimental design model, namely in this design there were 2 systems, the first system was treated, the second system was not given treatment. The variations in treatment in this study are as follows; (1) Solar modules without using passive cooling reflectors (2) Solar modules using reflectors and passive cooling. Data were collected for 4 days from (08.00-14.00) with a sample of 50 Wp solar modules. The data collection technique used is literature study, performance and testing documentation. The results showed that the results of the solar panel testing power with 2 variations of treatment, namely; (1) Solar modules without the use of reflectors and passive cooling produce an average power of 47.68 watts (2) Solar modules using reflectors and passive cooling 59.63 watts. The results of this study indicate that solar modules using reflectors and coolers increase the power by 25.07% of solar modules without using reflectors and passive cooling.